The Analysis of Leakage Inductance for Planar Transformer - Bayramoglu, Halil; Akboy, Erdem (IEEE, 2025)
Planar transformers generally have lower leakage inductance than conventional transformers. For this reason, they are preferred in applications requiring high power density. Nowadays, higher power density converters are required. Therefore, several methods for decreasing leakage inductance have been researched to further increase power density in planar transformers. Winding interleaving is the best-known technique to decrease leakage inductance in planar transformers. However, it is difficult to provide an interleaved structure in transformers with a high turns ratio. In this paper aims to minimize leakage inductance in a 12:2:2 high turns ratio planar transformer for 280 W LLC converter by using secondary winding parallelization with interleaved structure. Leakage inductance is calculated using magneto motive force (MMF) method and finite element analysis (FEA) method is applied using ANSYS Maxwell for different interleaved winding structures in planar transformers. The effects of different interleaving winding structures on leakage inductance in planar transformers with secondary winding parallelization are presented.
Keywords: planar transformer; leakage inductance; magneto motive force (MMF); maxwell; interleaving; winding parallelization; DESIGN; Computer Science; Robotics